Hubungan Pengetahuan, Sikap dan Tindakan Mahasiswa dalam Penggunaan Masker yang Benar - Yunus Elon; Evelin Malinti; Reagen Mandias (Poltekkes Kemenkes Bengkulu, 2022)
Wearing masks is one of the important protocols in protecting yourself and others from the risk of transmitting COVID-19. This study aimed to evaluate the relationship between knowledge, attitude, and action. Students in using masks correctly. This research is quantitative research with a correlational approach. A total of 120 students at Adventist University Bandung, were selected using a non-probability sampling technique. Validity and reliability tests were carried out before distributing the questionnaire through the Google Form platform, with a cronbach alpha value of 0.602. This research has received an ethical certificate with the number 018/EKS-SU/II/21. The results of the univariate analysis showed that 90.0% of respondents had good knowledge, 97.5% had good attitudes and 73.3% had good actions. Bivariate analysis showed a significant and positive relationship between knowledge and attitudes r=.373 p-value=.000, there was also a significant and positive relationship between knowledge and action r=.049 p-value =.000. The conclusion of this study, the level of knowledge is positively and significantly correlated with attitudes and actions in using masks. The better the knowledge, the better the attitudes and actions.